Conferencing Otherwise: A Feminist New Materialist Writing Experiment - Jayne Osgood; Carol A Taylor; Camilla Eline Andersen; Angelo Benozzo; Neil Carey; Constance Elmenhorst; Nikki Fairchild; Mirka Koro-Ljungberg; Anna Moxnes; Ann Merete Otterstad; Teija Rantala; Karen Tobias-Green (United States, 2022)
This article attempts to reconfigure hegemonic framings of “the academic conference” and thereby offer a means to (re-)encounter the spatial, temporal, and affective forces that conferences generate, differently. We are a geographically dispersed but multiply entangled group of academic researchers united by theoretical fault lines within our work that seek to ask what if and what else. This “what if” and “what else” thinking has manifested in experimental and subversive doings otherwise at a series of academic conferences. The storying practices presented in this article were made possible by the vital materialism of a shared google.doc. It was within this virtual environment that we attempted to weave diffractive accounts of what conferencing otherwise produces. This writing experiment offers a series of speculative provocations and counter-provocations to ask what else does conferencing make possible. This article is an invitation to the reader to plunge in and wallow within the speculative accounts which ensue and to contemplate the possibilities of breaking free from sedimented ways of neoliberal conferencing.